2009
DOI: 10.1016/j.febslet.2009.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Rab35 – A vesicular traffic‐regulating small GTPase with actin modulating roles

Abstract: a b s t r a c tThe Rab family of GTPases are regulators of eukaryotic vesicular membrane traffic, while modulation of actin dynamics is a function conventionally associated with the Rho family of GTPases. Rab35 is a Rab protein with both plasma membrane and endosomal localization, and has been implicated in diverse processes that include T-cell receptor recycling, oocyte yolk protein recycling and cytokinesis. Rab35 regulates neurite outgrowth in neuronal-like cells, and can induce protrusions even in typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 58 publications
0
44
0
Order By: Relevance
“…Furthermore, a possible role of Rab35 in CLIC4-mediated cell adhesion remains to be established. One difficulty with such studies is that (1) the precise function of CLIC4 remains elusive, and (2) Rab35 acts on at least six distinct effectors, consistent with Rab35 mediating numerous processes, and that its activity is regulated by multiple guanine-nucleotide-exchange factors and GTPaseactivating proteins Chua et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a possible role of Rab35 in CLIC4-mediated cell adhesion remains to be established. One difficulty with such studies is that (1) the precise function of CLIC4 remains elusive, and (2) Rab35 acts on at least six distinct effectors, consistent with Rab35 mediating numerous processes, and that its activity is regulated by multiple guanine-nucleotide-exchange factors and GTPaseactivating proteins Chua et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We next examined Rab35, which has recently emerged as a regulator of endocytic recycling (Allaire et al, 2010;Allaire et al, 2013;Chua et al, 2010;Kouranti et al, 2006). In serumstarved HeLa cells, Rab35 was mostly found at the plasma membrane and, to a lesser extent, in intracellular compartments (Fig.…”
Section: Clic4 Is Not Required For Egfr Traffickingmentioning
confidence: 99%
“…At this point, the cell must proceed to the final cytokinetic event, abscission, leading to the resolution of the ICB. Recent work has demonstrated that remarkable changes occur inside the ICB, such as the reorganization of post-Golgi vesicle trafficking (Chua et al, 2010;Gromley et al, 2005;Wilson et al, 2005) and increases in ICB microtubule dynamics (Connell et al, 2009;Fanarraga et al, 2010). However, the molecular machinery and the mechanisms that mediate abscission during cytokinesis remain to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…94 The silencing of Rab35 inhibited cell migration in MCF7 breast cancer cells. 95 Conversely, Rab35 mitigates cell migration in brain tumor cells 52 that suggests that Rabs GTPase modulation of cell migration may be tissue specific.…”
Section: 93mentioning
confidence: 99%